EFEKTIVITAS MODEL PIMCA DENGAN MULTI-REPRESENTASI PADA PEMBELAJARAN GERAK LURUS BERUBAH BERATURAN (GLBB) KELAS X IPA DI SMA KATOLIK THOMAS AQUINO MANADO - Christo Palit; Cosmas Poluakan; Jimmy Lolowang (Charm Sains: Jurnal Pendidikan Fisika, 2022)
This study aims to determine the increase in student learning outcomes in physics subjects by the PIMCA (Presentation, Idea Mapping, Conceptualizations, Formative Assessment) model with multi-representation in Uniformly Changing Straight Motion (GLBB). The type of research carried out was quantitative with the Pre-Experiment Design method because there was only one treatment group that was chosen to determine the achievement of learning outcomes and the research design used was the one grub pretest-posttest design. The instrument used is the Pre-test to test the students' initial abilities, then they are given treatment, namely PIMCA and finally the Post-test is given to find out the results after the treatment is applied. The research is located at Thomas Aquino Catholic High School Manado. The sample tested was class X IPA 1 academic year in the odd semester 2020/2021 with a total of 20 students as respondents. The results of data processing and analysis obtained the average value of the Pre-test 28 and the average value of the Post-test 71 and carried out statistical testing with the paired sample test t-test obtained a sig. (2-tailed) value of 0.000 <0.05 so there is an increase in student physics learning outcomes after the treatment is applied.